Diversity and Dynamics of Yeasts During Vidal Blanc Icewine Fermentation: A Strategy of the Combination of Culture-Dependent and High-Throughput Sequencing Approaches - Jing Li (Frontiers in Microbiology, 2019)
In this study, attention has been focused on the ecology of yeasts during the spontaneous and inoculated fermentation processes of Vidal blanc icewine in northeast China, which is very important for screening autochthonous yeast strains, understanding the roles of these strains, and managing fermentation. The strategies were to conduct spontaneous and inoculated laboratory-scale fermentation processes simultaneously and to analyze the samples taken at different fermentation stages by culture-dependent and -independent methods. Three hundred and thirty-eight yeast strains were isolated and twelve genera were identified by sequencing. During the spontaneous fermentation process, non-Saccharomyces yeasts were predominant in the initial and middle stages, whereas Saccharomyces dominated in the later stages; Candida was preponderant in the whole process, and its abundance in the final stages was only lower than Saccharomyces. The inoculated fermentation was characterized by a predominance of Saccharomyces throughout the fermentation process; non-Saccharomyces yeasts were observed in the early stage. The internal transcribed spacer (ITS) 2 region gene was firstly used to analyze the yeast diversity in the samples during the icewine fermentation processes by high-throughput sequencing (HTS), and a more complex mycobiota was revealed. Moreover, the dynamics of other major fungi (mainly Davidiella and Alternaria) during icewine fermentation processes were also revealed, which have never been reported in icewine before.